Eight weeks of creatine monohydrate supplementation is associated with increased muscle strength and size in Alzheimer’s disease: data from a single-arm pilot study - Smith, Aaron N.; Sullivan, Debra K.; Morris, Jill K.; Carbuhn, Aaron F.; Herda, Trent J.; Taylor, Matthew K. (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the potential muscular benefits of an eight-week creatine monohydrate (CrM) supplementation in patients with Alzheimer’s disease (AD).MethodsThis single-arm pilot trial, conducted at the University of Kansas Medical Center in Kansas City, examined the intervention-associated changes in muscle strength, muscle size, and neuromuscular junction (NMJ) integrity following 8 weeks of CrM supplementation (20 g/day) in 20 participants with AD. All participants completed handgrip-strength measurements on the dominant hand (highest of three trials in kg of force). Ten participants completed lower body strength assessment via leg dynamometry at three velocities (1.05 rad∙s−1, 2.10 rad∙s−1, 3.14 rad∙s−1), with peak torque (in Newton-meters) recorded over five repetitions. Eighteen participants completed muscle size assessment by ultrasound measurement of cross-sectional area (mCSA, cm2) in the rectus femoris and vastus medialis, as well as muscle thickness (cm) in the rectus femoris, vastus medialis, and vastus lateralis. NMJ integrity was assessed in 19 participants by measuring plasma C-terminal agrin fragment (CAF) levels. All assessments were measured at baseline and 8 weeks.ResultsFollowing 8 weeks of CrM, mean hand-grip strength increased by 1.9 kg from baseline (p = 0.02). Lower leg strength did not change for any velocity among the ten participants who completed leg dynamometry. mCSA (n = 18) increased from baseline in the rectus femoris (p = 0.03) and vastus medialis (p = 0.01), but muscle thickness (n = 18) did not change in the rectus femoris (p = 0.41), vastus medialis (p = 0.37), nor vastus lateralis (p = 0.17). Subcutaneous fat (n = 18) decreased in the rectus femoris region (p = 0.006) and vastus lateralis region (p = 0.003), with no change in the vastus medialis region (p = 0.52). Mean CAF (n = 19) values did not change (p = 0.46).ConclusionThis eight-week pilot trial suggests that 20 g/day of CrM may provide modest skeletal muscle benefits in patients with AD. These data provide preliminary evidence to warrant further investigation of the potential for CrM to prevent AD-related decline in muscle function.Clinical trial registrationClinicalTrials.gov, identifier NCT05383833.